2016
DOI: 10.1108/medar-05-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning

Abstract: Purpose Positioned within a framework of challenges facing universities, this paper aims to focus on challenges faced by teachers of accounting as a business discipline to ensure it remains relevant in a fast-moving and changing environment. Design/methodology/approach Drawing on a variety of sources, this paper explores a number of issues surrounding teaching and learning in the current university environment. The seven papers that make up the special issue are located within a framework which is used to il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Furthermore, respondents suggested that the managers of distance education should involve industry in curriculum design (11%) and establish a careers guidance service (4%). These findings are in line with the arguments of Samkin and Stainbank (2016) and Nesaratnam and Gayen (2018), who advocate for stakeholder participation in the design of more integrative lifelong learning opportunities in HEIs’ curricula. Other factors in improving employability, such as professional courses and the creation of career centres, were also suggested by a small percentage of respondents (see Figure 2).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, respondents suggested that the managers of distance education should involve industry in curriculum design (11%) and establish a careers guidance service (4%). These findings are in line with the arguments of Samkin and Stainbank (2016) and Nesaratnam and Gayen (2018), who advocate for stakeholder participation in the design of more integrative lifelong learning opportunities in HEIs’ curricula. Other factors in improving employability, such as professional courses and the creation of career centres, were also suggested by a small percentage of respondents (see Figure 2).…”
Section: Resultssupporting
confidence: 88%
“…Many scholars have identified a mismatch between the competencies and skills developed by graduates through their education and the requirements of industry. For instance, Samkin and Stainbank (2016) noted that the curricula of higher education institutions (HEIs) have not succeeded in preparing work-ready graduates to meet the changing skill requirements of employers. Moreover, Nesaratnam and Gayen (2018) observed that, despite the growing calls from stakeholders for HEIs to develop employable skills in graduates, business communities continue to lament the lack of graduates who meet employers’ requirements and expectations.…”
mentioning
confidence: 99%
“…(p. 231) Scholars reflecting on the occurrences within the EU since Marginson and Considine (2000) have noted the profound changes in the L&T function of universities. Measurement and monitoring of L&T performance has escalated, with a greater focus on student teaching evaluations (Hazelkorn, 2015;Samkin and Stainbank, 2016). As predicted by Marginson and Considine (2000), external benchmarking mechanisms in L&T have also become ubiquitous.…”
Section: Research and The Impact Of Research Ranking Systemsmentioning
confidence: 99%
“…University graduates around the world are facing the challenge of a precipitous trend of unemployment (Rae, 2008;Thern, et.al, 2017). Samkin and Stainbank (2016) raised the argument that, the curriculum of Higher Education Institutions (HEIs) failed to prepare work-ready graduates to meet employers" expectation in terms of skills, attributes and professional qualities. This thrusts forward the notion that graduate employability requires graduates to be equipped with the necessary attributes and skills aligned to the requirements of the labor market.…”
Section: Introductionmentioning
confidence: 99%